Rare case of implantable cardioverter defibrillator infection caused by Stenotrophomonas maltophilia and Pantoea calida. Issue 8 (30th August 2019) - Ajam, Mustafa; Shokr, Mohamed; Ajam, Firas; Lieberman, Randy
Abstract : Despite the numerous advancements in cardiac implantable electronic defibrillator (CIED) designs and implantation techniques, device-related infections continue to represent significant morbidity and mortality. Although Gram-positive bacteria remain the most commonly reported organisms, various other bacterial families have been reported. We describe a 61-year-old patient with a history of non-ischaemic cardiomyopathy who presented with implantable cardioverter defibrillator pocket infection due to Stenotrophomonas maltophilia and Pantoea calida that developed a few days following the device generator replacement. Early device explantation, tissue sampling and initiation of sensitivity-directed antibiotics are necessary steps for early diagnosis and management of such CIED-related infections. S. maltophilia and P. calida should be added to the expanding list of the causative organisms behind CIED-related infections. Our case and available literature demonstrated excellent sensitivity of these two organisms to sulfamethoxazole-trimethoprim treatment.